Exploring Individual Foundations of Marital Relationship Sustainability in Women with Veteran Spouses: A Phenomenological Study - Bakhtyar Hassan Muhammadamin (Iranian Evolutionary Educational Psychology Journal)
Objective: The aim of this research was to explore the personal foundations of marital relationship sustainability in women with veteran spouses. Methods: The current study employed a qualitative interpretative phenomenological research design. Among women with veteran spouses (Iran-Iraq War veterans), 14 individuals from Sardasht city (Iran) were selected purposively and interviewed. The interviews were analyzed using the interpretative phenomenological analysis method. Results: Exploring the lived experiences of these individuals led to the identification of 18 sub-themes and six main themes (love, spirituality, conscientiousness, perception of meaning, social connectedness, and high acceptance). These findings reveal the reality that sustaining a lasting interaction and coping with marital life challenges with a veteran spouse may be achievable through the core elements of love, spirituality, conscientiousness, perception of meaning, social connectedness, and high acceptance. Conclusions: Counselors and psychologists working in the field of marriage and family can foster these dimensions in individuals to facilitate successful entry into marital life and the continuous sustainability of relationships.